Effectiveness Of Allotment Penalty Imposed By Judge In The Case Of Children For A Child Protection As Victims (Case Study at State Court of Sumber) - Didi Wahyudi Sunansyah; Aryani Witasari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The formulation in this study were 1) How allotment setting penalty in child protection legislation in order to protect the child as a victim? 2) How is the effectiveness of the penalty in the Child Protection Act?Method sociological approach juridical law and specification in this study were included descriptive analysis. Even sources and types of data in this study are primary data obtained from interviews with field studies Supervising Officers Society Child (PK Child) of the Penal Hall Cirebon and Head of Correctional Cirebon, And secondary data obtained from the study of literature. Data were analyzed qualitatively. The problems studied by the theory of progressive legal protection and law.Based on the results of this study concluded under Appropriation settings Criminal Penalty In Child Protection Act is not describe protect children as victims, because the penalty to be paid by the convict is intended for countries not intended for children who are victims of crime. Appropriation effectiveness Criminal Judge Penalty That Dropped In Case of Children in the Context of the Protection of Children As Victims are Criminal penalties in the Law on Child Protection was not effective in reality, as more convicts chose imprisonment in lieu of penalty are not paid, compared to paying the penalty, it has implications for the expenditure of state finances are more likely to pay for convicts in prisons and to make prisons more crowded or over capacity.Keywords: Effectiveness; Penalty; Justice; Protection; Child.